A sustainable multi-function biomorphic material for pollution remediation or UV absorption: aerosol assisted preparation of highly porous ZnO-based materials from cork templates - Quarta, Alessandra (2019)
For the first time, highly porous ZnO-based biomorphic materials were synthesised using cork as a natural sustainable template. In the first step, waste cork powder was pyrolysed and converted into inorganic carbon. This template was then infiltrated using a novel approach employing an aerosol of zinc-containing solutions. The infiltrated powders were calcined to convert the precursors into zinc oxide. Depending on temperature, these could form either a ZnO-graphite composite material, or pure ZnO. Their morphology, porosity, microstructure and composition were characterised; their optical band gap energies, ability to adsorb and photodegrade organic pollutants and UV absorption were also assessed. When heated to 350 °C they maintained the 3D porous cork structure, producing a graphite-containing composite material, with both physical adsorption and photocatalytic activity (Eg = 3.19 eV), suitable for environmental remediation. When heated to 700 °C, the powders were pure ZnO (no graphite), and they absorbed in the UV region, hence suitable for use as sunscreen. Doped ZnO ecoceramics were also produced, using silver and aluminium. An addition of 1 mol% Ag improved photocatalysis under solar light. Conversely, adding 2 mol% Al and calcining at 700 °C deactivated photocatalysis, but maintained strong UV absorption, producing a safer sunscreen material (no generation of free radicals). This is the first time that photocatalytic or UV absorption properties of any wood-derived biomorphic material or ecoceramic have been reported.